Racial diversity and social capital : equality and community in America - Hero, Rodney E., 1953-; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
Race and racial diversity are important aspects of America and have been shown to substantially affect social relations and the political system, often in ways inconsistent with the values of equality. However, greater civic association and a general sense of community, embodied in the concept of social capital, are said to have tremendous beneficial effects and profoundly influence American society. This 2007 study juxtaposes and critically assesses two bodies of research that have reached different conclusions on these issues. Is America's legacy of racial inequality an 'evil twin' of the benefits of social capital? By analysing the social outcomes for racial minorities, in addition to other dimensions of American politics, the author shows that the impact of racial diversity consistently outweighs that of social capital.
Introduction -- The social capital thesis -- The racial diversity thesis -- Examining social outcomes, and civic and economic equality -- Voter turnout and other forms of participation in context / with Caroline Tolbert -- Public policy outputs -- Conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cultural pluralism -- United States; Minorities -- United States; Social capital (Sociology) -- United States; Social participation -- United States; Equality -- United States; Race awareness -- United States; United States -- Social conditions -- 1980-; Electronic books